Literature Review The Implementation Of Infection Prevention And Control Programs On The Medical Staff - Gilang Indhira Mustika; Kusbaryanto Kusbaryanto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
Health-related infection (HAI) is a major problem facing hospitals affecting patients as well as healthcare workers around the world. There have not been many published systematic reviews on the implementation of infection prevention and control programs. The aim of this systematic review is to analyze the implementation of infection prevention and control programs in medical personnel. The research phase begins with the formulation of a research question (RQ) and data collection begins with a search for research with qualitative methods at Pubmed, Science Direct, Proquest, GARUDA and Google Scholar on "infection prevention and control", "IPC management", and "the implementation process. IPC "for health personnel, published between January 2015 and June 2020. A total of 106 publications were taken, method and abstract screening were conducted (n = 106), research was issued (n = 91), full text reviewed (n = 14) , articles that issue n = 0). Synthesized article (n = 14). Based on the maipcng results of 14 articles regarding the implementation of infection prevention and control programs for medical personnel, they are grouped into research focus and paper type categories. Gaps were identified related to lack of knowledge, awareness and commitment to the importance of IPC during health service delivery. Management needs to provide support with training, funding for the IPC program so that it supports infrastructure. Human resource factors and other supporting factors contribute to the implementation of IPC so as to reduce the incidence of infection